Connecting Particle Fracture with Electrochemical Impedance in LiXMn2O4. Issue 14 (1st January 2017) - McGrogan, Frank P.; Bishop, Sean R.; Chiang, Yet-Ming; Van Vliet, Krystyn J.
Abstract : Li-ion battery (LIB) electrodes subjected to repeated electrochemical cycling exhibit limited lifetime and gradual performance loss. Fracture of the active electrode particles, though one of the most widely discussed degradation mechanisms, is still not understood fully in even the most studied positive electrode systems. Here, we develop the connection between fracture and impedance in LiX Mn2 O4 composite electrodes via cycling schedules designed to produce discrete fracture events. We establish a correlation between these fracture events and acoustic emissions, as well as a parallel correlation between acoustic emissions and impedance growth. Through extensive impedance analysis, including conversion of impedance data to distributions of relaxation times, we identify the sources of impedance growth as electronic contact impedance and ionic surface layer impedance. Through measurements at multiple temperatures, we also estimate activation energies of ∼0.1 eV for electrolyte resistance, bulk contact resistance, and current collector resistance, ∼0.4 eV for charge-transfer resistance, and ∼0.3 eV for cathode surface layer resistance. We thus demonstrate a direct and correlative relationship between electrochemomechanical fatigue and performance loss, which can inform LIB design and characterization for improved longevity and late-life performance.